Reduction of Digitalization Policy in Indonesian MSMEs and Implications for Sharia Economic Development - Reza Octavia Kusumaningtyas; Rahayu Subekti; Abdul Kadir Jaelani; Asron Orsantinutsakul; Utkarsh K Mishra (Institut Agama Islam Negeri Batusangkar, 2022)
Micro, Small, and Medium Enterprises are one of Indonesia's economic buffer pillars. However, its position as a financial buffer still faces various problems. The purpose of this research is to examine the reduction of digitalization policies for Indonesian MSMEs and their implications for the development of the Islamic economy. This research is normative legal research with a statutory approach. The results showed that the provisions in the Copyright Law that require the digitization of MSMEs make its management more efficient and straightforward. During the COVID-19 pandemic, there has been a twofold increase in the number of businesses transitioning to the digital ecosystem. MSMEs are present in the development of the Islamic economy, with the possibility of managing MSMEs in the technology-based halal industry. Deregulation is carried out by simplifying regulations in order to improve the flow of bureaucracy. However, behind the ease, there are obstacles experienced by MSMEs in their digitalization efforts, including blocks in terms of community culture, regulation, and structure